Determination of assurance сoefficient by supporting structures fatigue of car bodies during transportation by the railway ferries - A. A. Lovskaya (Nauka ta progres transportu, 2014)
Purpose. To determine assurance coefficient by supporting structures fatigue of car bodies during transportation by the railway ferries. Methodology. The operating conditions of cars in international railway-water communication have been investigated in previous works for the solution of this problem. To solve the problem there were conducted researches of dynamic features of car bodies transporting by the railway ferries in conditions of the sea storm. A mathematical model of car bodies movement was made up and accelerations acting on them in placements on the decks were determined. During determination of accelerations the actual meteorological characteristics of the Black Sea during a storm were taken into account. The assurance coefficient fatigue by supporting structures of car bodies by the railway ferries was determined and it was found that under regular loading of the car body n ≈ 2,0 . It is higher than the admissible value. Findings. Comparison of obtained acceleration values with the accelerations acting on car bodies when operating on main-line routes showed that they have exceeded the acceleration specified in the regulations approximately on 40%. It proves the need of accounting the loads acting on car bodies during transportations by the railway ferries when designing new generation cars. Originality. There was proposed a mathematical model of car bodies movement by the railway ferries in the conditions of sea storm. It gives the possibility of determining the accelerations of car bodies placed on the decker rail ferries taking into account the hydrometeorology characteristics. Practical value. The results of researches can be used when designing new generation cars to provide their strength during the combination of railway and water transportation. It gives an opportunity to develop measures as to the adaptation of cars bodies to the interaction with the fastenings of railway ferries by means of equipping their bearing constructions with special fastening assembly units. Such technical solution will allow decreasing expenses for unscheduled repair of cars while transporting them by railway ferries and providing safety of combined transport traffic.